Peran Polres Sukabumi dalam Penanganan Prostitusi Online Berdasarkan UU Nomor 21 Tahun 2007 (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This study examines the role of the Sukabumi District Police (Polres) in tackling online prostitution cases based on Law Number 21 of 2007 concerning the Eradication of Human Trafficking Crimes. Online prostitution has rapidly developed with the advancement of information and communication technology, where perpetrators use social media and messaging applications to offer sexual services anonymously. This study employs a qualitative method with a normative juridical approach, involving in-depth interviews with police officers, legal document analysis, and field observations. The results indicate that the Sukabumi District Police face various challenges, including limited human resources and technology, as well as difficulties in cooperating with internet service providers. Nevertheless, the Sukabumi District Police have implemented various strategies, such as enhancing digital forensics capabilities and public awareness campaigns, to address these issues. The study concludes that law enforcement against online prostitution requires collaborative efforts between law enforcement officers, internet service providers, and the community. The recommendations generated include increasing the capacity of police personnel in digital forensics and improving cross-agency cooperation for more effective law enforcement.